Synthesis of cross-linked carboxymethyl cellulose and poly (2-acrylamido-2-methylpropane sulfonic acid) hydrogel for sustained drug release optimized by Box-Behnken Design - Akram Ashames; Fahad Pervaiz; Moawia Al-Tabakha; Kanza Khalid; Nageeb Hassan; Hina Shoukat; Manal Buabeid; Ghulam Murtaza (Journal of Saudi Chemical Society)
This research aims to fabricate and characterize chemically crosslinked CMC/PVP-co-poly (AMPS) based hydrogel for the sustained release of model drug metoprolol tartrate through the free radical polymerization technique. Box-Behnken Design was used to optimize CMC/PVP-co-poly (AMPS) hydrogel by varying the content of reactants such as; polymers (CMC and PVP), monomer (AMPS), and crosslinker (EGDMA). Carboxymethyl cellulose (CMC) was crosslinked chemically with AMPS with a constant ratio of PVP by the ethylene glycol dimethacrylate as the crosslinker in the presence of sodium hydrogen sulfite (SHS)/ammonium peroxodisulfate (APS) as initiators. After developing CMC-based hydrogels using different polymers, monomer, and crosslinker concentrations, this study encompassed dynamic swelling, sol–gel fraction, drug release and chemical characterizations such as FTIR, XRD, TGA, DSC, and SEM. In vitro drug release and swelling were performed at 1.2 and 6.8 pH to determine the sustained release pattern and pH-responsive behavior. These parameters depended on the crosslinker, polymer, and monomer ratios used in the formulation development. XRD, SEM, and FTIR showed the successful grafting of constituents resulting in the formation of a stable hydrogel. DSC and TGA confirmed the thermodynamic stability of the hydrogel. Hydrogel swelling was increased with an increase in the ratio of monomer; however, an increase in the ratio of polymer and crosslinker decreased the hydrogel swelling. In vitro gel fraction and drug release also depended on polymer, monomer, and crosslinker ratios. The fabricated CMC/PVP-co-poly (AMPS) hydrogels constituted a potential system for sustained drug delivery.